234 Clinicians with lupus losing skills and diversity from health services results from an on-line survey. (April 2019) - Booth, Sara; Price, Elizabeth; Walker, Elizabeth
Abstract : Background: It is well-documented that people with systemic lupus erythematosus (SLE) have high levels of workplace disability and unemployment. We present the data from a sub-group of participants in an on-line survey designed to understand the barriers and facilitators to employment in people with lupus as a first step towards solutions. Three hundred and ninety-three detailed questionnaires were returned, demonstrating that the overarching barriers to continuing employment were fluctuation, invisibility and fatigue, facilitators were flexibility in working pattern, part-time working understanding management and colleagues. Participants suffered from high levels of anxiety and distress about their loss of income and likely future inability to work. Those claiming benefits felt guilt, shame and humiliation. Methods: The on-line survey was conducted in UK adults with SLE, through the LUPUS UK website, and was designed to find out about the difficulties and successes that people with SLE have in maintaining employment. The data from participants working in a clinical profession or employed by the National Health Service (NHS) in a clinicalrelated activity were identified from the cohort. Their data is currently being analysed to see if those working in NHS organisations have consistently good experiences of workplace support and better chances of retention. Results: Fifty-five of the sample of 393 (14%) worked or had worked in the NHS in a clinical or clinically-related role. Roles include doctors, managers clinical coders, midwives, podiatrists, pharmacists, operating department assistants. The largest group were nurses including two in senior roles and untrained nursing assistants. Most of the sample had reduced hours or stopped working completely directly as a result of lupus, support was variable with some attributing workplace flexibility to NHS employment but others experiencing harassment. A recently introduced method of calculating sick leave militates against people with fluctuating conditions. Conclusions: SLE presents specific difficulties for maintaining employment fatigue, fluctuation and invisibility not addressed by current anti-discrimination legislation or currently-available reasonable adjustments. As Europes largest employer with a core mission of treating illness the NHS could set an example of how to overcome barriers to employment in people with fluctuating conditions, like lupus. There is clear evidence of loss of skills from the organisation and emerging evidence from this study suggest variable support and levels of knowledge form managers and colleagues. Personal pain from loss of role and income were high in participants. Further data will be available. Funding Source(s): No external funding required